Community Helpers at the Construction Site - Schuh, Mari C. 1975- (North Mankato, Minnesota : Little Pebble Books, an imprint of Capstone Press, 2017)
"Nonfiction, simple text with full-color photography presenting community helpers on the scene of a construction site"--
A new home -- At the job site.
Includes bibliographical references and index.
Ages 4-8.
K to grade 3.
Accelerated Reader AR
Keywords: Construction workers -- Juvenile literature; Construction industry -- Juvenile literature